al-Imtiyāz bain al-ḥaqīqat va al-majāz : masā̕il-i ʻilm-i gẖaib, istimdād, taṣarruf-i auliyā̕ Allāh par ek lājavāb kitāb - Ḥalvā̕ī, Muḥammad Nabī Baḵẖsh (Maktabah-yi Nabaviyah, 1978)
Refutation of the Ahl-i Hadith criticism of the beliefs of Sunni (Barelvi) Muslims.